Analysis of the mylohyoid nerve in elderly Japanese cadavers for dental implant surgery. Issue 1 (23rd November 2020) - Koga, Shintaro; Sato, Iwao; Li, Zhong‐Lian; Miyaso, Hidenobu; Kawata, Shinichi; Itoh, Masahiro
Abstract: Objectives: Injury to the mandibular nerve (MN) branches may cause pain and irregular occlusal movement during mastication after mandibular dental treatments. Growing evidence indicates that the calcitonin gene‐related peptide (CGRP) plays a key role in the development of peripheral sensitization and the associated enhanced pain, suggesting it may be a sign to ensure a safe and reliable dental implant treatment. Our focus was on the distribution of the MN branches and their communication with the lingual nerve (LN), the localized expression of CGRP, and the identification of a pain area related to the mylohyoid muscle (MM) fascia in the mandibular floor. Material and Methods: In this study, MM samples from 440 sides of 303 human cadavers aged 61–103 years were examined microscopically and immunohistochemically. These data were further evaluated by the use of principal component analysis. Results: A complex but weak attachment site was identified for the fascia of the MM. CGRP expression was mainly located in small vessels and was scattered throughout the whole fascia of the MM. Communication between the MN and LN was found in 62.5% (275/440) of the samples. The results from the principal component analysis showed that the positive contributions were from the descending branch in the premolar region (correlation coefficient value R = 0.665), the ascending branch in the molar region ( R = 0.709) and the intermediate branch of the digastric branch ( R = 0.720) in component 1. In the fascia off the MM, strongly labeled CGRP‐positive cells were also found around the blood vessels and the nerve. Conclusions: The findings reported in this study indicate that there is a risk of damage when pulling the fascia off the MM at the border of the molar and premolar regions during dental implant surgery.